Effects of Sowing Dates on Yield and Yield Components of Different Varieties of Wheat (Triticum aestivum L.) in Western Uttar Pradesh - Singh, Y. P.; Singh, Satybhan; Dhangrah, V. K.; Mishra, Tripuresh (International Journal of Economic Plants, 2021)
An experiment was conducted during Rabi season (November-December) of 2018–19 to study the effect of three dates of sowing (26th November, 11th December and 25th December) on growth, yield attributes and yield of fivewheat varieties (HD-2967, HD-3086, WH-1105, PBW-343 and PBW-226) at Agricultural Research Farm of IFTM University, Moradabad (UP) India. The experiment was laid out in Factorial Randomized Design with two replications. Sowing was done at spacing of 22.5 cm in sandy loam soil. The observations were recorded on growth, flowering, maturity, yield and yield components. Analysis of variance showed the significant variations were observed for the characters viz. plant height, days to flowering, spikes per plant, days to maturity, grain yield, test weight, straw yield, biological yield and harvest index due to changing dates of sowing. However, varietal variations were recorded for plant height, days to flowering, spikes per plant, days to maturity and test weight. Wheat sown on 26th November recorded significant increase in plant height, tillers plant-1, spikes-1 plant, grain yield and straw yield over late sowing on 11th December and 25th December. There was no significant variation among varieties for yield and yield contributing traits such as grains spike-1, grain and straw yield. Significant interaction effects between dates of sowing and varieties were found for days to flowering which showed that the variety HD-2967 is as best wheat variety for early sown and PBW-226 for late sown conditions in order to obtain better returns.